치위생과와 비보건학과 일부 여대생의 손톱 내 불소농도 차이 - 오나래; Na-rae Oh; 박의정; Eui Jung Park; 윤성욱; Sung-uk Yoon (Han'guk Ch'iwisaeng Hakhoe chi, 2016)
Objectives: The purpose of the study is to investigate the relationship between fluorine concentration within finger nails and the level of dentifrice in dental hygiene students and non-health majoring students. Methods: A self-reported questionnaire was completed by seventy female college students living in Daegu and Gyeongbuk that are not supplied with fluoridation from May to June, 2014. Informed consent was approved by institutional review board (IRB). The questionnaire consisted of general characteristics of the subjects (11 items) and oral health behavior including number of tooth brushing, duration of tooth brushing, number of mouth rinsing, and amount of dentifrice. A dentist and a dental hygienist examined directly the subjects by the guideline of World Health Organization (WHO). The oral examination included decayed tooth, healthy tooth, and filled tooth. The nail samples were obtained from seventy female students. Results: Comparing the dental hygiene students and non-health majoring students, 62.5% of dental hygiene students used approximately 1300mg of dentifrice and 55.2% of non-health majoring students used 1800mg or more of dentifrice. The non-health majoring students used more dentifrice (p<0.01). The fluorine concentration within nails was 1.9905㎕/g in dental hygiene students and 3.2149㎕/g in non-health majoring students. The fluorine concentration within nails in the dental hygiene students was significantly lower(p<0.01). Conclusions: The accumulation of fluoride in human body is not fully caused by dentifrice. However, The accumulation may occur due to tooth brushing so that it is necessary to educate the students about the right use of the dentifrice.